Living high - training low: Effect on erythropoiesis and aerobic performance in highly trained cross-country skiers - Robach, P.; Schmitt, L.; Brugniaux, J.; Nicolet, G.; Duvallet, A.; Fouillot, J.-P.; Pialoux, V.; Moutereau, S.; Lasne, F. (13. International Hypoxia-Symposium, February, 19-22, 2003, Banff, Alberta (Kanada), 2003)
OBJECTIVES: 1) to verify whether the "living high—training low" method improves red cell mass and maximal aerobic performance, 2) to assess whether markers may predict the individual tolerance for this training method. METHODS: leven athletes (6 men, 5 women) performed a 18-day training period at 1100m, by sleeping either at 1100m (Control, n 5 5, VO2max 5 596 9ml/min/kg) or in hypoxic rooms (Hypoxia (10h/24h), n 5 6, VO2max 5 62 6 4ml/min/kg), the O2 fraction corresponding to 2500m, 3000m and 3500m (3 3 6days). Evaluation was conducted at 1100m, before and 15 days after the end of the training period. Measurements were VO2max (treadmill), time to exhaustion at the velocity at VO2max (Texh), hemoglobin (Hb), hematocrit (Hct), reticulocyte count (RETIC), erythropoietin (EPO), ferritin (Ferrit), serum transferring receptor (sTfR), red cell volume (RCV, CO-rebreathing method). All blood markers (except RCV) were also measured at the end of each altitude stage. Further, before training, all subjects performed a VO2max test at 2500m and spent 3h at rest at 3000m (Hacute). Training load was recorded during the whole study. RESULTS: Training load during the study was similar between the two groups. Neither VO2max, nor Texh were significantly modified by training, both in control (22.5% and 214.8%, respectively, n 5 5) and in hypoxia groups (23.9% and 215%, respectively, n 5 5). In Hypoxia group, VO2max was found higher (n 5 1), unchanged (n 5 1) and lower (n 5 3), assuming a variation .5%. Training coupled with hypoxic nights increased Hb, Hct, EPO, sTfR, whereas no change occurred in Control group. RETIC, VGR and Ferrit were not modified in Hypoxia group. Hacute increased EPO in both groups. However, in Hypoxia group, the changes in aerobic performance (after—before) were related neither to the decrement in VO2max at 2500m, nor to the EPO increase in Hacute. CONCLUSION: The present results indicate that 18 days of "living high—training low" stimulated erythropoiesis. However, two weeks after the end of this protocol, hematological parameters had returned to normal values, and aerobic performance was not found increased. This study was supported by grants from the International Olympic Committee and the French Ministry of Sports.